2022
DOI: 10.1111/vru.13163
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in veterinary diagnostic imaging: A literature review

Abstract: Artificial intelligence in veterinary medicine is an emerging field. Machine learning, a subfield of artificial intelligence, allows computer programs to analyze large imaging datasets and learn to perform tasks relevant to veterinary diagnostic imaging. This review summarizes the small, yet growing body of artificial intelligence literature in veterinary imaging, provides necessary background to understand these papers, and provides author commentary on the state of the field. To date, less than 40 peer-revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 76 publications
(227 reference statements)
0
33
0
Order By: Relevance
“…With advances in technology, digital storage capabilities, and accessibility, images are being used as a diagnostic tool when veterinarians are not present at the time of animal necropsy, especially due to time and location constraints [ 19 ]. More recently, image classification and automated machine learning have been implemented in human and veterinary medicine as auxiliary diagnostic tools [ 20 , 21 , 24 , 25 ]. Similar technology was applied to identify postmortem organ images in humans, and it is expected to assist human disease diagnosis in the near future [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…With advances in technology, digital storage capabilities, and accessibility, images are being used as a diagnostic tool when veterinarians are not present at the time of animal necropsy, especially due to time and location constraints [ 19 ]. More recently, image classification and automated machine learning have been implemented in human and veterinary medicine as auxiliary diagnostic tools [ 20 , 21 , 24 , 25 ]. Similar technology was applied to identify postmortem organ images in humans, and it is expected to assist human disease diagnosis in the near future [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, as well as in humans, automated technology for wound management could help to quickly assess the severity of an open wound that may require prompt intervention in acute injuries [ 7 , 8 , 9 ]; likewise, it may objectify the state of the wound at the time of clinical presentation. Automated solutions for wound management may help in the monitoring of the subsequent wound healing process.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent studies have demonstrated artificial intelligence's (AI) ability to evaluate a range of canine thoracic radiographic features such as cardiac size, pulmonary patterns, and pleural changes. [1][2][3][4][5][6][7][8][9][10][11] Although the practicality of AI in veterinary diagnostic imaging is not yet fully established, several commercial AI platforms are currently available to the practitioner. Further independent scrutiny of these tools is necessary to validate these products, in large part so that practitioners can build confidence in their application.…”
Section: Introductionmentioning
confidence: 99%